Financial Statement Analysis of Manado State University - Freddy S. Kawatu; Ramon A.F. Tumiwa; Cecilia Lelly Kewo (AIBPM Publisher, 2019)
Manado State University had applied Government Regulation No.71st 2010, but effectively in 2015. To understand the financial performance of the institution, financial statement during 2017 and 2018 could be examine and analyze with the realized budget. Quality financial statement have a trait that could be understand, relevant, comparable, and reliable. Other than that, quality of financial statement could be expressed with auditor’s opinion. Based on inspection result by Audit Board of the Republic of Indonesia at March 2017, there is a flaw in internal control system for drafting financial statement at Manado State University. Mainly on administrating and account for the financial administration, also the application of the Government Regulation No.71 article 4th and 7th2010 about accrual base government accounting standard still not optimal. The focus on this research is that how the financial statement present by Manado State University is suitable with Government Regulation No.71article 4th and 7th2010 about accrual base government accounting standard? And how is the internal control system in the drafting of financial statement at Manado State University?